Digital Curation and Information Design in digital environments: women's museums panorama - Vicentini Jorente, Maria Jose [UNESP]; Silva, Stephanie Cerqueira [UNESP]; Padua, Mariana Cantisani [UNESP] (Pontificia Universidade Catolica Campinas, 2021)
Women's museums take on significant functions for social discussions which, through preservation and access to the memory and culture of their collections, provide new habits and perspectives on objects constituted by structures of multiple languages on the Web. In this perspective, this study aims to understand how Digital Curation and Information Design in Information Science contribute to information presentation, access and sharing in these digital environments on the Web. The general objective was to contextualize the concepts and definitions of Digital Curation and Information Design to identify possible articulations for information organization and its presentation of women's museums digital collections. The study is qualitative in nature and descriptive-exploratory. It consisted of a bibliographic review of the themes correlated with data collection in the scope of collections and digital environments of women's museums, through information from the International Association of Women's Museums and Patrimonio en Femenino. The results showed a low number of digital collections available and also the need for reflection on the methodology of planning and creating digital environments as a laboratorial process, continuous, in perpetual beta, iterative and in successive improvements. The study concluded that other dimensions of women's memory preservation should be constituted to facilitate information access and sharing with the implementation of Digital Curation and Information Design resources for the construction of environments and, in them, their collections.
Keywords: Digital curation; Digital museums; Genre; Information design; Women's museums